Istiqra Al Ma'nawiy's Reasoning: As a Model of Indigenzation and Contextualization of Islamic Law (Hazairin and Hasbi Ash Shiddiqiy's Thought) - Isman; Risdayani (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This paper examines Asy Syatibi's legal reasoning of istiqra al-ma'nawy (thematic induction) and its impact on Indonesia's indigenization and contextualization of Islamic law. The reasoning model of Istiqra al-Ma'nawy Asy Syatibi was the study's first focus. Hazairin and Hasbi Ash Shiddiqiey are efforts to indigenize and contextualize Islam through the use of Istiqra al-Ma'nawy's method in Islamic legal reasoning. Doctrinal or normative legal research with a philosophical viewpoint A documentation model is used to collect data. This study's analytical method uses interpretive, idealistic, and holistic meta-logic. The notion of